The geomechanical strength of carbonate rock in Kinta valley, Ipoh, Perak Malaysia - Mazlan, N.A. (American Institute of Physics Inc., 2018)
The stability of both cut rocks and underground openings were influenced by the geomechanical strength of rock materials, while the strength characteristics are influenced by both material characteristics and the condition of weathering. This paper present a systematic approach to quantify the rock material strength characteristics for material failure and material & discontinuities failure by using uniaxial compressive strength, point load strength index and Brazilian tensile strength for carbonate rocks. Statistical analysis of the results at 95 percent confidence level showed that the mean value of compressive strength, point load strength index and Brazilian tensile strength for with material failure and material & discontinuities failure were 76.8 ± 4.5 and 41.2 ± 4.1 MPa with standard deviation of 15.2 and 6.5 MPa, respectively. The point load strength index for material failure and material & discontinuities failure were 3.1 ± 0.2 MPa and 1.8 ± 0.3 MPa with standard deviation of 0.9 and 0.6 MPa, respectively. The Brazilian tensile strength with material failure and material & discontinuities failure were 7.1 ± 0.3 MPa and 4.1 ± 0.3 MPa with standard deviation of 1.4 and 0.6 MPa, respectively. The results of this research revealed that the geomechanical strengths of rock material of carbonate rocks for material & discontinuities failure deteriorates approximately from material failure. © 2018 Author(s).